Effect Of Online (Social) Media Influencers On Consumer Purchase Intent: A Young Generation Perspective - Patil , Swati; Wani , Nitin (Gyan Management Journal, 2024)
The growing use of online (social) media and mobile technologiesmade it easy for people to generate content and share details abouttheir personal lives online. This has created an environment thathas contributed to the rise of online (social) media influencers, acommunity of operators who attained a level of notoriety similar tothat of celebrities in the online world. With the decreasing efficacy ofconventional advertising strategies, more professionals have realisedin recent years the importance of online (social) media influencersin promoting awareness of brand and sparking buyer dialogues (Louet. al.,2021). In recent times, a increasing number of professionalsacknowledged the significance of online (social) media influencersin augmenting brand recognition and adopting consumer dialogues,mainly considering their diminished efficacy of conventionalmarketing strategies (Baker 2021)
Keywords: Growing; Online; Influencers; Social Media; Consumer